Scientific Research in the Faculty of Dentistry "Raúl González Sánchez". 2011-2015 - Sol Ángel Rosales Reyes; Rosa María González Ramos; Edelis Raymundo Padrón; Luis Hernández Pedroso; Orietta Valverde Grandal (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Universities are an excellent place to do research.  The main function is to generate new knowledge. Objective: To evaluate the actions developed and the results achieved in the Research Department of the Faculty of Dentistry "Raúl González Sánchez" of the University of Medical Sciences of Havana, in the 2011-2015 period. Materials and Methods: A descriptive study of the actions performed and the results achieved was carried out in the Research Department at institutional level, in the 2011 - 2015 period. Institutional actions carried out in favor of research were studied, as well as the variables associated with scientific research projects and the publications made. Results: Training workshops were held for the development of research projects and publications, as well as workshops for the approval of 129 new projects. Of the total number of projects, 25,4% belonged to the Periodontics department, 22,2% to Orthodontics, 18,3% to Prosthodontics, and 16,3% to Comprehensive General Dentistry.  Therewas a total of 581 publications, and 175 were related to projects.  The preferred place to publish were the peer-reviewed journals (52.4%); of which, 22,2% were published in foreign journals. The 67,3% of the articles were original. Conclusions: Between 2011 and 2015, the research activity in the Faculty studied can be evaluated as satisfactory, since there has been an increase in the number of research projects and the publications have remained at similar levels for years; except 2015, in which they increased. The number of publications resulting from projects increased, too. More than half of the articles were published in peer-reviewed journals, the number of papers in foreign journals increased, and most of them were original articles.  Keywords: Projects, research, publication, scientific production, Faculty of Dentistry.